HAMBATAN BELAJAR SISWA BERDASARKAN PENALARAN ANALOGI DALAM MATERI ARITMATIKA SOSIAL DI SEKOLAH MENENGAH PERTAMA - Chanisah Chanisah; Sugiatno Sugiatno; Silvia Sayu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study is entitled "Student Learning Obstacles Based on Analogy Reasoning in Social Arithmetic Material in Junior High Schools". The research method used is descriptive method with the form of case study research. The subjects of this study were students of class VII A Pontianak State Middle School consisting of 32 students. The results showed that student learning barriers based on the analogy reasoning in the social arithmetic material include: (1) Based on the components of thinking Encoding students do not experience obstacles and can identify the characteristics or structure of the problem sources and target problems; (2) Based on the components of Inferring thinking, there are students who experience obstacles in finding relationships in the source problem; (3) Based on the components of Mapping thinking, students experience obstacles in finding relationships or solutions found in the target problem; (4) Based on the components of Applying thinking, students experience obstacles in calculating the target number and choosing the right formula. Keywords: Analogy Reasoning, Learning Obstacles, Social Arithmetic